COMBAT THE ILLEGAL DISTRIBUTION OF DRUGS AND PSYCHOTROPIC SUBSTANCES INTERNATIONAL CONTRACTUAL BASIS AND CHARACTERISTICS OF DETENTION OF THIS CATEGORY OF CRIMINALS - Oyatullo Khalimovich Karimov (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the international contractual basis of the fight against the illegal distribution of narcotic drugs and psychotropic substances and the features of arresting this category of criminals. In the article, the formation of the fight against the illegal distribution of narcotic drugs and psychotropic substances and the international agreements adopted in this direction are thoroughly studied. As a central element of the article, the features of seizure, entities and procedures of seizure strengthened in the international agreements on the fight against the illegal distribution of narcotic drugs and psychotropic substances. Because of the conducted research, the characteristics of the considered contracts, their advantages and disadvantages have been revealed. Based on the results of the analysis, some suggestions have been made.